2015
DOI: 10.5897/ajb2014.14331
|View full text |Cite
|
Sign up to set email alerts
|

Production of lignocellulolytic enzymes from three white-rot fungi by solid-state fermentation and mathematical modeling

Abstract: Three species of white rot-fungi (Pleurotus ostreatus, Coriolus versicolor, and Lentinula edodes) were grown on 12 solid media based on several lignocellulosic materials (oak sawdust, coconut husks, coffee husks and corn bran) during 49 days. The media had varied carbon/nitrogen ratios and CuSO 4 content. The objective of the work was to evaluate the effect of the media formulation on the production of lignocellulolytic enzymes and degradation of lignocellulosic components by the three fungal species. C. versi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 32 publications
0
8
0
10
Order By: Relevance
“…However, because of the higher cost, using a large amount of organic nitrogen source such as yeast extract was not the most efficient method for industrial enzyme production. Our research did not show the best result of endoglucanase production, however, it indicated the potential of polypore fungi M. xanthopus strain KA038 to produce better cellulolytic activity compared with other polypore fungi such as Melanoporia sp., Pycnoporus sanguineus , Pycnoporus coccineus and Coriolus versicolor (Montoya et al, 2015; Onofre et al, 2015; Chuwech et al, 2016; de Oliveira et al, 2016). Thus, this result demonstrated that M. xanthopus was a remarkable species of polypore fungi in producing endoglucanase activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, because of the higher cost, using a large amount of organic nitrogen source such as yeast extract was not the most efficient method for industrial enzyme production. Our research did not show the best result of endoglucanase production, however, it indicated the potential of polypore fungi M. xanthopus strain KA038 to produce better cellulolytic activity compared with other polypore fungi such as Melanoporia sp., Pycnoporus sanguineus , Pycnoporus coccineus and Coriolus versicolor (Montoya et al, 2015; Onofre et al, 2015; Chuwech et al, 2016; de Oliveira et al, 2016). Thus, this result demonstrated that M. xanthopus was a remarkable species of polypore fungi in producing endoglucanase activity.…”
Section: Discussionmentioning
confidence: 99%
“…It was speculated that the degradation of alkali lignin was dominated by MnP. MnP was considered to be the main enzyme involved in the partial mineralization of a broad spectrum of aromatic substances (Parikh et al, 2014).…”
Section: Antagonistic Experimentsmentioning
confidence: 99%
“…Específicamente, las enzimas degradadoras de lignina (ligninasas) se han empleado en el tratamiento de aguas residuales, en la degradación de colorantes sintéticos en aguas de la industria textil, en el blanqueamiento de pulpa en la industria papelera, y en la degradación y mineralización de hidrocarburos aromáticos, pesticidas y otros contaminantes nitro-aromáticos [4,5]. Las ligninasas también se han empleado en la industria de alimentos para animales ya que mejoran las propiedades nutricionales de los forrajes al posibilitar la deslignificación de materias primas lignocelulósicas particularmente en el caso de los rumiantes [6].…”
Section: Introductionunclassified
“…Pese al esfuerzo que se ha realizado por esclarecer la acción directa que ejercen los metales sobre la activación de las ligninasas, así como sobre las concentraciones óptimas de estos metales inductores para la síntesis de estas enzimas por hongos macromicetos, se requiere investigar el efecto de estos metales en el caso de cultivos en estado sólido teniendo en cuenta que la mayoría de los estudios se han enfocado en procesos de fermentación sumergida. En un trabajo previo [6], se estudió el efecto de la relación C/N y de la adición de Cu2+ a medios sólidos basados en aserrín de roble, capacho de coco, cascarilla de café y salvado de maíz sobre la producción de enzimas lignocelulolíticas por T. versicolor. Sin embargo, se requiere esclarecer el efecto inductor del cobre y del manganeso sobre la síntesis de estas enzimas lignocelulolíticas a partir de este tipo de residuos agroindustriales en fermentación en estado sólido.…”
Section: Introductionunclassified
See 1 more Smart Citation